Self-Identification in Literature: the Case of Writers of Greek Cypriot Descent in Australia - Herodotou, Maria (Études helléniques / Hellenic Studies, 1999)
Greek Cypriots in Australia is a sub-group of the Greek Diaspora. Migration from Cyprus to Australia is relatively recent in comparison with migrations from Greece. Most migrated in the 60’s and mainly after the Turkish invasion of Cyprus in 1974. Many of the Greek Cypriot writers, therefore, were born there and their bonds with their mother country are very strong. Its unresolved political problem strengthens these bonds. This paper examines how Greek writers of Cypriot descent in Australia identify themselves with Greece, Cyprus and Australia as a place and as a culture. The writers are distinguished into three broad categories depending on the language they use (English, Greek & English, Greek). The use of language is an indication of the extent of their connection to a particular place. That doesn’t mean that language is the most important factor of their identity. The Anglophone writers (and some of the bilinguals), for example, combine both cultures and this creates a tension or even a conflict which is evident in their work, while the Hellenophones are more at case with their Greek identity. They develop a nostalgia for Cyprus and try to recreate or reconstruct, in a painful way, the place and its culture. For all writers, Greece and Hellenism become a conceptual world. It is evident that identification is a process, a search for an identity which is never static but fluid.